Recent advances in the use of Galleria mellonella model to study immune responses against human pathogens - Pereira, Thais Cristine [UNESP]; Barros, Patrícia Pimentel de [UNESP]; de Oliveira Fugisaki, Luciana Ruano [UNESP]; Rossoni, Rodnei Dennis [UNESP]; Ribeiro, Felipe de Camargo [UNESP]; Menezes, Raquel Teles de [UNESP]; Junqueira, Juliana Campos [UNESP]; Scorzoni, Liliana [UNESP] (MDPI, 2018)
The use of invertebrates for in vivo studies in microbiology is well established in the scientific community. Larvae of Galleria mellonella are a widely used model for studying pathogenesis, the efficacy of new antimicrobial compounds, and immune responses. The immune system of G. mellonella larvae is structurally and functionally similar to the innate immune response of mammals, which makes this model suitable for such studies. In this review, cellular responses (hemocytes activity: phagocytosis, nodulation, and encapsulation) and humoral responses (reactions or soluble molecules released in the hemolymph as antimicrobial peptides, melanization, clotting, free radical production, and primary immunization) are discussed, highlighting the use of G. mellonella as a model of immune response to different human pathogenic microorganisms.
Keywords: Antimicrobial peptides; Clotting; Experimental model; Free radical production; Galleria mellonella; Hemocytes; Immune response; In vivo study; Melanization; Primary immunization